Policy and trend analysis for the creation of IP convergence content cluster - Chae, Uri; Lee, Insoo; Lee, Jooyeoun (Proceedings - 2021 IEEE International Conference on Big Data and Smart Computing, BigComp 2021, 2021)
In the era of the 4th industrial revolution, convergence of content IP has become important, and effective support is needed to activate convergence. In order to propose a solution for this, an analysis of policies and trends for the establishment of an IP convergence content cluster was conducted. The purpose of this thesis is to propose an efficient and competitive plan based on this by analyzing Korea and other countries status and policy implications. The research was conducted with Korea and other countries policy analysis, content industry, cluster, and Korea and other countries analysis. In the policy analysis, the high-level policies of the Ministry of Culture, Sports and Tourism and related ministries were analyzed, and related policies of other countries' were analyzed. Content industry analysis derives the changing aspect of the content industry and the direction of convergence. Cluster trends analyzed the recent trends pursuing social innovation. The Korea and other countries case analysis investigated the general status and location environment of existing facilities and content convergence support organizations. As the content industry is planning to actively nurture the content industry as a new growth engine for the future, We hope that it will be established as a landmark for global content convergence through cooperation between each ministry and local governments. As the content industry is planning to actively foster globally as a new growth engine for the future, we hope that it will be established as a landmark for global content convergence through cooperation between each ministry and local governments.
Keywords: Content industry; Global contents; High level policies; Industrial revolutions; Local government; Policy analysis; Policy implications; Social innovations; 4th Industrial Revolusion; Contents Cluster; IP (Intellectual Property); Knowledge creation; New business